Management of hyperkalemia at the emergency service of a general hospital - Herrera Añazco, Percy (2014)
Hyperkalemia (HK) is a common and potentially fatal emergency services (1) pathology. As a result, timely and appropriate care, the same as in the context of a structure of limited attention by cumbersome bureaucratic processes and overcrowding emergency services-as presented in the hospitals of the Ministry of Health (MOH) is required - can translate into delayed diagnosis and initiation of therapy as well as in poor therapeutic indications with complications resulting in patient death (2).